Intervention program on family communication addressed to fathers and mothers with teenage daughters in conflict with the criminal law assisted in the Attention Entity Acarigua II (H) Portuguesa state (Boletin Médico de Postgrado, 2021)
The main aim of this research is to propose an intervention program on family communication aimed at fathers and mothers with teenage daughters in conflict with the Criminal Law assisted in the Acarigua II Attention Entity (H), Portuguesa state; the quantitative methodology was used under the modality of Feasible Project, developing the first three parts of the project the included diagnosis, feasibility study and proposal design. The study population consisted of twenty-five (25) parents, mothers or representatives present during the months of October 2017-February 2018. To determine the communication model of parents, a self-applied family communication questionnaire which was submitted to expert judgment and pilot test was conducted. The analysis of the data revealed that the predominant communication model was the leveler although with marked fluctuations between the models. A feasibility study was carried out that included a market, institutional, social and financial study, confirming the feasibility of the proposal. Finally the program was design under the modality of five theoretical - practical workshops with the aim to self - assess the way in which parents and teenage daughters communicate while promoting the acquisition of new communication guidelines predominantly of the leveling model type.
Keywords: family relations; communications; adolescent behavior; penal responsibility; conflict, psychological